PERAN SISTEM MULAZAMAH DALAM MEWUJUDKAN TUJUAN PENDIDIKAN ISLAM - Amir Sahidin (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Islamic education which is held using the traditional system today is illustrated by the mulazamah system. The mulazamah system is a system that previously gave birth to scholars who were very influential in the development of Islam. Therefore, this system needs to be studied more deeply both in terms of management and methodologies to find out its role in realizing the goals of Islamic education. Through an authoritative literature review, it can be concluded, although the mulazamah system management does not have definite rules, but methodologically, the mulazamah system has its own advantages and disadvantages. The drawback is that it takes a long time; scientific quality is highly dependent on the teacher; can only be followed by certain people; and there is no regular management. While the advantages, forming students to become experts in the science being studied; there is a chain of knowledge; students only learn the required knowledge; and it doesn't cost much. From these advantages it appears that the mulazamah system has a role in realizing the goals of Islamic education, namely being able to give birth to a complete human being in order to realize devotion to Allah.